Local government financial distress: international comparison and latest developments in the light of the Italian spending review approach - Paolo RICCI; Renato CIVITILLO (Revista de Management Comparat International)
Although it is not difficult to note the increasing number of financial crises in the public sector field (municipalities, counties, states, etc.), it is quite easy to see that most of the literature has focused mainly on pathological situations occurred in private companies (Cahill and James, 1992; Honadle, 2003; Migliaccio, 2012). The key question, therefore, lies in the consequences for stakeholders involved arising from different remedies. USA and Italy legal system provides for a mechanism to be used trying to heal the crisis but they are forms of intervention after the crisis. The real question is to clarify why, today, is relatively simple and common for local governments to have over-spending crisis. The answer to this question lies, probably, in the correct vision and understanding of public administration and, in particular, of local government.